Relationship of Managerial Creativity With Demographic Variables: Enhancing Organizational Effectiveness through Managerial Creativity (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The concept of organizational effectiveness is animportant innovation in business management. Initially, organizationaleffectiveness focused on how well an organization compete, how quickly theybring products to the market, their status in the community, theirattractiveness to potential market and their profitability. In other words,organizational effectiveness considers how well an organization performsbusiness. Instead of defining corporate success by a few short-term measures,such as sales or profit, it fostered a holistic long-term perspective. Thisexpanded perspective that resulted from a focus on the overall effectiveness ofan organization has become central to corporate survival and success in today’seconomy. The focus on people, their performance, innovation and creativity isthe professional concern of organizational effectiveness. The current researchattempts to define a broad perspective on organizational effectiveness and itsrelation to managerial creativity.  Withheightened levels of competition and an uncertain economic environment, manyorganizations are encouraging their teams to be more creative so as to enhancetheir competitive edge. In the past, organizations mainly focused on producingin bulk and selling at targeted margin as there were very few competitors andbuyers didn’t have significant bargaining power. But with the advancement oftechnology and globalization, buyers’ power has grown significantly and it isforcing companies to be highly innovative and customer centric. In thisbackdrop, it becomes quite imperative to deploy all their resources in a waythat help them create more value for the customers. This makes it important formanagers to adopt a management style that encourages employees to come up withnew ideas that can enhance productivity.